Efficacy of modified EDAS combined with a superficial temporal fascia attachment-dural reversal surgery for the precise treatment of ischemic cerebrovascular disease - Nuerlanbieke, Hanati; Niyazi, Ailiyaer; Wu, Qinfen; Yuan, Yang; Habudele, Zanghaer; Dun, Xiaoyi; Wei, RuRui; Aisha, Abudula (Frontiers in Surgery, 2023)
Objective: To investigate the potential therapeutic benefits of Modified EDAS combined with superficial temporal fascia attachment-dural reversal surgery for the treatment of ischemic cerebrovascular disease. Methods: Retrospective analysis was made on the clinical data of 33 patients with ischemic cerebrovascular disease, who were admitted to the Neurological Diagnosis and Treatment Center of the Second Affiliated Hospital of Xinjiang Medical University from December 2019 to June 2021. All patients were treated with Modified EDAS combined with superficial temporal fascia attachment-dural reversal surgery. At 3 months after operation, the outpatient department rechecked the patient's head CT perfusion imaging (CTP) to understand the intracranial cerebral blood flow perfusion. The DSA of the patient's head was re-examined 6 months after operation to observe the establishment of collateral circulation. The improved Rankin Rating Scale (mRS) score was used to evaluate the good prognosis rate of patients at 6 months after surgery. The mRS score ≤ 2 was defined as good prognosis. Results: The preoperative cerebral blood flow (CBF), local blood flow peak time (rTTP), and local mean transit time (rMTT) of 33 patients were 28.235 mL/(100g ·min), 17.702 s, 9.796s, respectively. At 3 months after surgery, CBF, rTTP, and rMTT were 33.743 mL/(100g·min), 15.688s, and 8.100s, respectively, with significant differences (P<0.05). At 6 months after operation, the establishment of extracranial and extracranial collateral circulation was observed in all patients by re-examination of head DSA. At 6 months after operation, the good prognosis rate was 81.8%. Conclusion: The Modified EDAS combined with superficial temporal fascia attachment-dural reversal surgery is safe and effective in the treatment of ischemic cerebrovascular disease, which can significantly increase the establishment of collateral circulation in the operation area and improve the prognosis of patients.